Experimental study on properties of hybrid stable & surfactant-free nanofluids GNPs/CNCs (Graphene nanoplatelets/cellulose nanocrystal) in water/ethylene glycol mixture for heat transfer application - M., Sandhya; D., Ramasamy; K., Kadirgama; W. S. W., Harun; R., Saidur (Elsevier, 2022)
The heat transfer capacity of any thermal cooling system depends on two factors, i.e., the selection of the coolant and the geometrical pattern of the approach. This article summarizes nanofluids' preparation ranging from 0.01 % to 0.2 % using Graphene nanoplatelets & CNC dispersed in a base fluid. The combination of water with ethylene glycol (EG) is a form of customary heat transmit liquids regularly utilized in numerous energy practices to maintain the water's decent cooling (or heating) capability; thus, 60:40 ratio of EG: W mixture used as the base fluid for thermo-physical properties enhancements. These nanofluids prepared are not used with surfactants as it results in generating bubbles and contaminating the heat transfer channels, influencing the overall performance. XRD & FESEM techniques were used to analyze the surface. The investigated nanofluids remained stable, with no substantial sedimentation for 30 days. The results of GNPs/CNC nanofluids at 0.1% volume concentration has proper stability showing excellent colloidal stability in the base fluid of EG: W at a ratio of 60:40. The present hybrid nanofluid has the ability to switch the traditional heat transfer fluids leading to efficient & compact thermal structures.